2017
DOI: 10.1111/ajt.13928
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcomes Related to Mycophenolate Exposure in Female Kidney Transplant Recipients

Abstract: In 2012, the U.S. Food and Drug Administration issued guidelines advising kidney transplant recipients (KTRs) to discontinue mycophenolate (MPA) in preparation for pregnancy. Little is known about how this guidance has affected pregnancy and graft outcomes. The purpose of this retrospective cohort study was to investigate any association between the discontinuation of MPA and KTR pregnancy and graft outcomes. Data from the National Transplantation Pregnancy Registry included 382 cases in which KTRs managed on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Ironically, discontinuing MPA during the second trimester or later significantly increased the risk of miscarriages and birth defects. 19 The drug's benefits may outweigh its risks in most people. However, it is important that all women of reproductive potential prior to being treated with MFS or MMF have proper education and counseling about pregnancy prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Ironically, discontinuing MPA during the second trimester or later significantly increased the risk of miscarriages and birth defects. 19 The drug's benefits may outweigh its risks in most people. However, it is important that all women of reproductive potential prior to being treated with MFS or MMF have proper education and counseling about pregnancy prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Leukopaenia or thrombocytopenia may also occur. Recent data indicate that MMF should be discontinued 6 weeks before a planned pregnancy …”
Section: Systemic Anti‐inflammatory Treatmentmentioning
confidence: 99%
“…In fact, a systematic review showed that as primary immunosuppression, MMF treatment was more effective than AZA in reducing the risk of acute rejection, by approximately 30% . In contrast, a recent study reported the importance of long‐term MMF discontinuation to graft survival postpartum (compared <6 weeks with >6 weeks prior to pregnancy; 5‐year graft loss: odds ratio, 5.56; 95% confidence interval, 1.38–22.22; P = 0.016) . These results not only support the current guideline consensus regarding MMF discontinuation at pregnancy but also raise an issue about the anti‐rejection effects of immunosuppressive agents during pregnancy in kidney transplant recipients.…”
Section: Discussionmentioning
confidence: 52%
“…Regarding the teratogenic effects of MMF, such as hypoplastic nails, cleft palate, facial malformation, and Tetralogy of Fallot, it is commonly accepted that MMF should be discontinued and changed to another immunosuppressant, such as AZA, more than 6 weeks before a planned pregnancy or upon the desire to bear children . Our patient was switched from MMF to AZA at 3 years before pregnancy; therefore, these changes could have caused the DSA and rejection.…”
Section: Discussionmentioning
confidence: 95%